A new formulation of the minimum variation log-aesthetic surface for scale-invariance and parameterization-independence. Issue 5 (3rd September 2018) - Suzuki, Sho; Gobithaasan, R.U.; Usuki, Shin; Miura, Kenjiro T.
ABSTRACT: The log-aesthetic curve, which includes the logarithmic (equiangular) spiral, clothoid, and circular involute, achieves control over the curvature distribution by defining its shape as an integral of its curvature, and is expected to be utilized for the field of aesthetic design. Some formulations of the log-aesthetic surface as extensions of the log-aesthetic curve have been proposed. The minimum variation surface is one of them, and has a feature that it can be used for arbitrary four boundary curves. The minimum variation log-aesthetic surface is defined as a surface which minimizes an objective function. However, it is not scale-invariant and parameterization-independent. In this study, we propose a new formulation of the minimum variation log-aesthetic surface for scale-invariance and parameterization-independence. GRAPHICAL ABSTRACT: